Параметры расчета прочностных характеристик аварийно-спасательного подъемного устройства для эвакуации людей и грузов - Makarevich С.; Makarevich Д. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
Article is devoted to a question of carrying out the power analysis of the precessional reducing mechanism with conic rollers, on the basis of which the small-sized manual, wich used in the rescue device for evacuation of people and freights from depth, is developed. Carrying out the power analysis of the precession reducing mechanism is necessary for optimization of gearing links parameters by criterion of a minimum of forces values and values of support in contacting links reactions and determination of forces in gearing values and of reactions of support values that will allow to make strength calculations of the precessional reducing mechanism links, including a choice of bearings. The design of the small-sized manual winch for the rescue device and its technical characteristics is given.